PRODUCTION OF AMBARELLA SEEDLINGS TREATED WITH INDOLE BUTYRIC ACID AND IRRIGATED WITH REUSED WATER - Queiroz, Jorge Luís Fabricio; Ferreira Neto, Miguel; Sá, Francisco Vanies da Silva; Porto Filho, Francisco de Queiroz; Lima, Yuri Bezerra de; Dias, Pollyana Mona Soares (Floresta, 2019)
Species of the genus Spondias, such as ambarella, are propagated primarily by vegetative parts. However, for planting it is necessary to use plant regulators. In addition to propagation related aspects, the availability of good quality water for seedling production in semi-arid regions is a limiting factor. The objective of this work was to evaluate the rooting of semi-herbaceous cuttings of ambarella using different concentrations of IBA conveyed in solution and talc, irrigated with different concentrations of treated domestic effluent. The experiment was carried out in a nursery with 50% shade in a completely randomized design in a 4 x 4 factorial scheme consisting of four doses of treated domestic effluent (EDT) diluted in water supply [E1 = 0% of EDT (100% AA - control); E2 = 33.3% of EDT (66.7% of AA); E3 = 66.7% of EDT (33.3% of AA) and E4 = 100% of EDT (0% AA)] used in daily irrigation and four IBA dilution managements (M1 = control without IBA, M2 = IBA carried in water at 6,000 mg L-1, M3 = IBA delivered in alcohol (70%) at 4,000 mg L-1 and M4 = IBA in Talc at 5000 mg L-1), with four replicates. The treated domestic effluent is viable for irrigation of ambarella seedlings in its diluted or concentrated. The use of 5,000 mg L-1 of IBA delivered to talc is management satisfactory for the propagation of seedlings of ambarella by means of semi-herbaceous cuttings.